Symbolic Cities in Caribbean Literature - Winks, C. author. aut Link
XVIII, 194 p.
Keywords: Utilizing cross-cultural strands, this comparative study analyzes Caribbean literary representations of magic and invisible cities reworking the notion of the city as both instituted social space and imaginary community.